Teaching Variation Development through tutoring in optimizing student achievement - Sura', Handayani; Sulaiman, Fitriyanti; Elihami, Elihami (Edumaspul: Jurnal Pendidikan, 2020)
Teaching studies regarding the study of developing teaching variations in facing industry 4.0 challenges. The approach commonly used in guidance activities is a group approach and an individual approach. A group approach is usually called group guidance and an individual approach is called individual counseling. Group guidance aims to help solve problems that are felt by groups of students through group activities, or problems that are individual in nature, namely those felt by an individual as an individual. members of the group. the purpose of this guidance effort includes five main functions that should be carried out by an independent person, namely; knowing yourself and the environment as it is, accepting yourself and the environment in a positive and dynamic manner, making decisions, directing yourself and making yourself happen.